Cyberbullies, cybervictims and cyberbullies-victims: Discriminant factors in portuguese adolescents - Carvalho,Marina (2017)
Enhancers of new and positive opportunities and learning, new technologies are also promoters of risks to the health and well-being of young people. Cyberbullying is one of those risks. The aim of this study was to analyse the differences between cyberbullies, cybervictims and cyberbully-victims for individual, relational and contextual factors. This is a Cross-sectional study. Results showed that cyberbully-victims reported higher alcohol consumption, as opposed to the increased drug use revealed by cyberbullies. Cybervictims reported more emotional symptoms, such as fear and sadness, and less night outs. Cyberbullies were more often involved in fights, and had an easier access to a larger amount of money and were more easy making friends, when compared to cybervictims. Based on the results, it is crucial to develop a greater awareness and education of parents and youth about the dangers of cyberbullying, together with the monitoring of technological development. A strong argument is also made related to the need of the inclusion of youth participation in the definition of public policies to prevent cyberbullying, as well as the need to focus not only in the prevention of cyber-peer related violence, but also to focus on violence-free, positive peer relationships, both virtual and in presence.